2010
DOI: 10.1007/s00540-010-0998-y
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil increases the incidence of mesenteric traction syndrome: preliminary randomized controlled trial

Abstract: The results of this study suggest that the use of remifentanil in laparotomy facilitates MTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Epidural anesthesia reduces SVR [ 26 ] due to sympatholysis as observed in the OE-group while SVR remained stable in the RE-group, besides a transitory increase may be due to CO 2 insufflation with release of hormones like noradrenalin, compression of the splanchnic organs, and CO 2 absorbed from the peritoneal cavity [ 27 , 28 ]. Moreover, traction of the viscera can stimulate release of vasoactive hormones like prostacyclin corroborating a decrease in SVR, more prevalent during open than laparoscopic surgery [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidural anesthesia reduces SVR [ 26 ] due to sympatholysis as observed in the OE-group while SVR remained stable in the RE-group, besides a transitory increase may be due to CO 2 insufflation with release of hormones like noradrenalin, compression of the splanchnic organs, and CO 2 absorbed from the peritoneal cavity [ 27 , 28 ]. Moreover, traction of the viscera can stimulate release of vasoactive hormones like prostacyclin corroborating a decrease in SVR, more prevalent during open than laparoscopic surgery [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma PGF-1 levels were measured prior to surgery and 20 minutes following skin incision. The study found that 40% of the patients receiving remifentanil developed MTS, while only 10% of patient's in the fentanyl group developed MTS [11]. Previous studies have shown the mechanism of action of remifentanil's vasodilation is likely due to enhanced secretion of nitric oxide and prostacyclin from endothelial cells [12].…”
Section: Prevention Of Mesenteric Traction Syndromementioning
confidence: 92%
“…In 2010, Y Nomura et al [11] published a study demonstrating that remifentanil infusions increased the likelihood of development of mesenteric traction syndrome. This study included 100 patients undergoing laparoscopic and open abdominal surgeries.…”
Section: Prevention Of Mesenteric Traction Syndromementioning
confidence: 99%
“…To confirm the synthesis of prostacyclin, which triggers MTS, we measured the levels of 6-keto-PGF1α, a stable metabolite of prostacyclin. Because a previous report described the mean onset time of MTS to be 16 ± 5 min after skin incision with symptoms persisting over approximately 30 min [ 16 ], blood was collected from an arterial line at the initiation of surgery (T0) as well as at 15, 30, and 60 min after the initiation of surgery (T15, T30, and T60, respectively). The samples were refrigerated and centrifugal separation was rapidly performed.…”
Section: Methodsmentioning
confidence: 99%